Chronic Elevation of Tumor Necrosis Factor-Alpha Suppresses Lactation via Downregulation of Lipoprotein Lipase. (7th June 2021) - Schozer, Frederick; Tso, Patrick; Karns, Rebekah; Wagner, Erin; Walker, Rachel; Hovey, Russell; Trott, Josephine; Riddle, Sarah; Thompson, Amy; Ward, Laura; Nommsen-Rivers, Laurie
Abstract: Objectives: Identification of physiologic factors that impede lactation is critical for developing interventions to support milk production. Our objective was to examine the role of tumor necrosis factor–alpha (TNF-A), a potent regulator of lipid metabolism, in the suppression of human lactation. We hypothesized that mothers with very low, versus sufficient milk production, would have elevated milk TNF-A and differential expression of TNF-A signaling pathways in the mammary epithelial cells (MECs). Methods: Among mothers in a study of low milk supply, extracellular mammary epithelial cell mRNA was isolated from fresh milk fat and submitted to RNA-sequencing. Aligned and quantified reads were examined for differentially expressed genes using t-tests (DEG, p < 0.05 after false discovery rate adjustment). We compared DEG in n = 5 with the lowest [LMP] (0–53 mL/24 h),  and n = 4 with the highest [HMP] (422–463 mL/24 h) milk production in the sampled breast, using PPAR, TNF-Alpha, and fatty acid biosynthesis KEGG pathways. BMI, fasting serum triglycerides, and milk TNF-A were also assessed. Results: Mean day postpartum (StdDev) was 32 (11) versus 47 (19) in LMP versus HMP, P > 0.05. Serum fasting triglyceride and BMI were significantly elevated in LMP versus HMP, P < 0.05. Median [min-max] TNF-A was 1.77 [0.64–6.89] pg/mL in LMP versus none detected in HMP (limit of detection, 0.50 pg/mL). Transcriptome analysis revealed 1.7-fold down regulation of lipoprotein lipase (LPL) in LMP versus HMP. PPARA and RXRA, regulatory factors upstream of LPL, were downregulated 1.8-fold. There was no difference in the expression of genes directly involved in fatty acid biosynthesis. Conclusions: Mothers with insufficient milk production have elevated milk TNF-A and a corresponding reduction in expression of lipid processing proteins known to be downregulated by TNF-A, notably LPL which is necessary for the hydrolysis of triglycerides into free fatty acids and glycerol for transport into MECs. We propose that TNF-A's disruption of critical fatty acid transport deprives the mammary gland of vital fuel and substrate towards the synthesis of human milk, without compensation through de novo lipid synthesis. Our findings shed light on TNF-A mediated lipid dysregulation as a potential link between obesity and insufficient lactation. Funding Sources: NIH and USDA.